Comportamiento de componentes agronómicos y de rendimiento bajo dosis crecientes de gallinaza en Eryngium foetidum L. “sacha culantro”, en Zungarococha-Loreto.2021 - Aricari Manuyama, Bremen Gabriel (2022)
The trial "Behavior of agronomic and yield components under increasing doses of gallinaza in Eryngium foetidum L. "sacha culantro", in Zungarococha-Loreto.2021", was developed in the experimental field of the Horticulture Workshop of the Faculty of Agronomy-UNAP. It was experimented with progressive doses of chicken on the agronomic characteristics and yield of the sacha culantro crop. The objective of the trial has been the determination of the behavior of the agronomic components and yield low progressive dose of chicken. The Experimental Design applied was that of Completely Random Blocks, with four treatments and four repetitions; a distance of 0.20 m x 0.20 m was used, where the following conclusions were reached: icken in Eryngium foetidum L. "sacha culantro", in Zungarococha had an effect on the behavior of agronomic and yield components; the T3 Treatment (20 t of hen/ha) presented the best results of the behavior of the agronomic and yield components; the T3 Treatment (20 t of chicken/ha) obtained the highest yield of plant weight/ha, with 18 t; the T3 Treatment (20 t of chicken/ha), had the highest economic income in the experiment with S/.58,954.00.